Causes of structural unemployment in Finland and Sweden 1990-2004 - Klas Fregert; Jaakko Pehkonen (Lund University, School of Economics and Management, Department of Economics, 2008)
We describe the size and timing for comprehensive as well as decomposed measures of unemployment. We then test for and confirm a change in the structural rate of unemployment by finding structural breaks in the Okun and Beveridge relations. Finally, we employ existing empirical models to examine the contributions of exogenous factors to the changes in the structural unemployment rate. We present separate estimates for the mid-1990s, late 1990s and early 2000s. They indicate that the structural rate has decreased in both countries, but has not returned to the levels of the 1980s.
Keywords: E24; E65; J64; 330; Structural unemployment; Okun curve; Beveridge curve; Finland; Sweden